Job Creation, Heterogeneous Workers and Technical Change: Matched Worker/Plant Data Evidence from Norway - Kjell G. Salvanes; Svein Erik Førre (Statistics Norway, Research Department, 2001)
Using matched worker/plant level data for Norway, theories explaining the change in skill composition are assessed using direct evidence on the job creation and destruction for high, medium and low skilled workers. Skill based job creation is analysed in detail for plants in a high-skill service sector and in low- and high-tech manufacturing sectors. Given a compressed wage structure in Norway and increased supply of high skilled workers, the supply of skills may also explain the changed skill composition. In order to disentangle the supply and demand effects, we fix the skill level by analysing the job creation process for skills within cohorts of workers.
Keywords: J23; J63; O33; 330; Job creation; heterogeneous workers; heterogeneous plants; technical change.